Mechanical anisotropy of paper-based all-cellulose composites. (October 2018) - Kröling, Henri; Duchemin, Benoît; Dormanns, Jan; Schabel, Samuel; Staiger, Mark P.
Abstract: The effects of fibre orientation and laminate stacking sequence on the mechanical anisotropy of paper-based all-cellulose composites produced via a partial dissolution route is examined. As part of this work, the fibre architecture and microstructure of the paper precursor is controlled and characterised in order to follow the anisotropy of the materials through from precursor to final composite material. The fibre orientation of the precursor was found to strongly influence the mechanical anisotropy of the final composite material. The ultimate tensile strength and Young's modulus of the paper-based all-cellulose composite laminates was 191 MPa and 17.5 GPa in the fibre direction, respectively, compared with 104 MPa and 10.4 GPa in the transverse direction, respectively. The ACC crystal structure was assessed with powder and transmission mode Wide-angle X-ray diffraction (WAXD) to measure the changes in crystallinity and crystal orientation due to the dissolution process. The mechanical response of multi-axial all-cellulose composite laminates was also determined experimentally and compared with analytical predictions by Classical Lamination Theory, demonstrating the utility of CLT for the prediction of the elastic properties of ACC laminates.